Pengembangan Media Diorama Sains Pada Materi Rantai Makanan Kelas V Sekolah Dasar Negeri Ellak Laok IV - Nurin Fardiana; Tita Tanjung Sari; Kadarisman (Jurnal Riset Madrasah Ibtidaiyah, 2023)
This study is developmental research that aims to determine how the use of science diorama media on food chain material Class V SDN Ellak Laok IV and find out how students respond to this research. Subjects in this study are students of Grade V SDN Ellak Laok IV with a total of 6 students. Data collection techniques in this study in the form of preliminary observations, and questionnaires/questionnaires. The procedures of this research are (1) potential and problems; (2) collecting information; (3) Product Design; (4) design validation; (5) design improvement; (6) product testing (7) product revision. The results of product validation include Media Design Validation with a percentage of assessment of 94% with criteria once and without revision, while the material validation with a percentage of assessment of 96% with criteria once and without revision. The results of the assessment of students ' response to the development of media diorama science categories were very good. This is evidenced by the value of the results of the student response questionnaire with an assessment of 95% and very good criteria. So that the development of Science diorama media is worthy of use as a learning medium. The results of data analysis in the form of Shiva's response to this development by 95%. So it can be concluded that the response of students to the development of science diorama media on food chain material of Class V SDN Ellak Laok IV is very good.